Q.S. Al-An'am Ayat 115 dalam Tradisi Khatamanan Al-Qur'an: Studi Living Qur'an di Pesantren Hidayatul Insan - Monica Putri (Jurnal Pendidikan Agama Islam, 2026)
This article examines the meaning and practice of Qur’an Surah Al-An‘am verse 115 within the tradition of Qur’anic khataman at Pondok Pesantren Hidayatul Insan using a Living Qur’an approach. The main objective of this study is to analyze how the verse is received and functioned in the ritual practice of Qur’anic khataman in the pesantren context. This research employs a qualitative method through a Living Qur’an framework, utilizing limited participatory observation and library research. The findings reveal that QS. Al-An‘am verse 115 is understood as a symbol of the perfection and absoluteness of divine revelation, affirming the finality of completing the Qur’an recitation. The recitation of this verse at the end of khataman serves not merely as a textual closure but also as a medium for internalizing theological values, strengthening the Qur’anic identity of students, and socially legitimizing the authority of the Qur’an. This study confirms that the Qur’an functions as a living text shaping the socio-religious reality of the pesantren